Direct radiative effect due to brownness in organic carbon aerosols generated from biomass combustion. (December 2016) - Rathod, T.D.; Sahu, S.K.; Tiwari, M.; Pandit, G.G.
Abstract: We report the enhancement in the direct radiative effect due the presence of Brown carbon (BrC) as a part of organic carbon aerosols. The optical properties of organic carbon aerosols generated from pyrolytic combustion of mango tree wood ( Magnifera Indica ) and dung cake at different temperatures were considered. Mie codes were used to calculate absorption and scattering coefficients coupled with experimentally derived imaginary complex refractive index. The direct radiative effect (DRE) for sampled organic carbon aerosols was estimated using a wavelength dependent radiative transfer equation. The BrC DRE was estimated taking virtually non absorbing organic aerosols as reference. The BrC DRE from wood and dung cake was compared at different combustion temperatures and conditions. The BrC contributed positively to the direct top of the atmosphere radiative effect. Dung cake generated BrC aerosols were found to be strongly light absorbing as compared to BrC from wood combustion. It was noted that radiative effects of BrC from wood depended on its generation temperature and conditions. For BrC aerosols from dung cake such strong dependence was not observed. The average BrC aerosol DRE values were 1.53±0.76 W g −1 and 17.84±6.45 W g −1 for wood and dung cake respectively. The DRE contribution of BrC aerosols came mainly (67–90%) from visible light absorption though they exhibited strong absorption in shorter wavelengths of the UV–visible spectrum. Highlights: Biomass fuels (wood and dung cake) were studied for brown carbon direct radiative effects. Model calculations predicted positive contribution of Brown carbon aerosols to organic carbon direct radiative effect. Average direct radiative values for brown carbon from dung cake were higher compare to wood. The visible light absorption played major role in brown carbon contribution (67–90 %) to total direct radiative effect.